INTERNAL MIGRATION TRENDS IN MALAYSIA - Saharani Abdul Rashid; Norshahida Saadan; Mazura Mokhtar (International Journal of Accounting, Finance and Business, 2023)
Migration is one of the important factors that affect population dynamics. The rapid urbanisation experienced by many developing countries has resulted in higher demand for urban space and services. The aim of this study is to add understanding of internal migration trends in Malaysia, by examining the migration statistics from the year 1980 to 2020. This paper discusses some empirical analysis to understand the dynamics of population movements in Malaysia and how it has shaped the population structure in the country. The urban and rural areas in Malaysia are shaped through time and by population shifts within and between its settlements. This study found that short distance migration is prominent in Malaysia, although the number of populations migrated from one area to the other have decreased in recent years. The rate of long-distance migration is also increasing which probably the result of higher standard of living and better transportation infrastructures and facilities. In general, most of the more developed states have higher in-migrants and all the less developed states have higher out-migrants during the more recent period. It can be concluded that development status of the state has attracted migrants from other states, probably in search of employment or other economic opportunities. This phenomenon resulting in the former states or areas suffering population declines or lower rates of growth.